Silane coupling agent modified metal oxide ink and preparation method and application thereof

A silane coupling agent modified metal oxide ink with fullerene derivatives addresses interface barriers in optoelectronic devices, enhancing electron injection and collection efficiency while offering stable, cost-effective film deposition for improved device performance.

CN113831786BActive Publication Date: 2024-12-31SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202010515508.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-06-08
Publication Date
2024-12-31
Estimated Expiration
2040-06-08

AI Technical Summary

Technical Problem

Existing optoelectronic devices face challenges with interface barriers between cathode and active layers due to mismatched work functions, leading to inefficient electron injection or collection, and current modification materials like polymers are costly, complex to prepare, and nanoparticle dispersions are unstable and prone to agglomeration.

Method used

A silane coupling agent modified metal oxide ink is prepared by combining metal oxide nanoparticles with long alkyl chain organic ligands and a silane coupling agent, forming a composite material that can be uniformly dispersed in solvent, allowing for stable deposition as a film by methods like spin coating or printing, and incorporating a fullerene derivative for improved conductivity and stability.

Benefits of technology

The modified metal oxide ink provides stable, cost-effective, and easily processable films that enhance electron injection and collection efficiency, reducing agglomeration and adsorption issues, thereby improving device performance and stability in optoelectronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113831786B_ABST
    Figure CN113831786B_ABST
Patent Text Reader

Abstract

The present invention discloses a silane coupling agent modified metal oxide ink and its preparation method and application. The preparation method comprises: firstly combining metal oxide nanoparticles with long alkyl chain organic ligands, and then performing surface modification with a silane coupling agent having a hydrophilic functional group to form metal oxide nanoparticles modified by a silane coupling agent, and then uniformly dispersing the metal oxide nanoparticles in a second organic solvent to obtain metal oxide ink modified by a silane coupling agent. The present invention also provides a metal oxide-fullerene derivative composite material, which comprises metal oxide nanoparticles modified by a silane coupling agent and a fullerene derivative. By means of the metal oxide ink, a metal oxide composite film can be made by spin coating, printing, etc., and the film can be used as an electrode modification layer in optoelectronic devices such as solar cells and light-emitting diodes to improve the contact performance between the electrode and the organic active layer, thereby improving the performance of the optoelectronic device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a metal oxide material, in particular to a nano metal oxide ink based on surface modification of a silane coupling agent, a composite material based on the metal oxide and a fullerene derivative, a film formed using the composite material, and the application of the composite material in optoelectronic devices, belonging to the technical field of optoelectronic semiconductor materials and devices. Background Art

[0002] Compared with traditional inorganic optoelectronic devices, new optoelectronic devices using organic semiconductor materials, such as organic solar cells, perovskite solar cells, organic light-emitting diodes (OLEDs), etc., can be processed by solution method, have the advantages of low cost, light material, easy large-area roll-to-roll production, etc., and have very broad application prospects. This type of new photoelectric conversion device usually has a sandwich multilayer structure, including an anode, an active layer and a cathode. Among them, the cathode mainly completes the electron injection (electroluminescent device) or collection (solar cell device) process. Common cathode electrode materials include: indium tin oxide electrode (ITO), fluorine-doped tin oxide (FTO), metal silver grid wire grid electrode, metal nanowire silver wire film electrode, metal film, such as aluminum electrode, silver electrode, etc. In many cases, the work function between the cathode and the photoelectric active layer does not match, and there is a large interface barrier for direct contact, which affects the injection or collection efficiency of electrons, and then affects the device performance. By introducing an interface modification layer between the cathode and the active layer, the work function of the electrode surface can be adjusted, so that an ohmic contact is formed between the electrode and the photoelectric active layer, thereby improving the injection or collection efficiency of electrons and achieving the purpose of improving device performance.

[0003] At present, the commonly used cathode modification materials include two categories: metal oxides and polymers. Polymer materials have the advantages of being processable in solution, compatible with printing methods, and having good film-forming properties. However, the synthesis and preparation methods of such polymer materials are relatively complex, and the material cost is relatively high. At the same time, due to the poor conductivity of polymers, when polymers are used as electrode interface modification layers, the device performance shows a very strong dependence on the film thickness, and the optimal thickness is usually below 10 nanometers, which brings great difficulty to the device preparation process. Metal oxides, such as zinc oxide, titanium oxide, and tin oxide, have the advantages of good conductivity and high material stability, and are a class of excellent electrode interface modification materials. The commonly used metal oxide film preparation mostly adopts the sol-gel method, spin coating the precursor solution and then sintering at high temperature, which is incompatible with the ink-based printing method. Another method is to reduce the particle size of the metal oxide to the nanoscale, and the metal oxide nanoparticles can be dispersed in the solvent, thereby meeting the requirements of solution method processing and preparation. For example, there are reports on the preparation of zinc oxide nanoparticles (ZnO) and titanium oxide nanoparticles (TiO 2 ) and cesium-doped titanium oxide nanoparticles (TiO2 :Cs) as an electrode modification layer effectively improves the device efficiency and device stability of organic solar cells [Adv.Mater.2012,24(38),5267-5272]. However, the stability of the nanoparticle dispersion itself is poor, the storage time is short, and it is easy to agglomerate during the printing process of thin film preparation, resulting in more film surface defects, and the rigidity is easy to break, which easily leads to device performance degradation or even short circuit [ACSAppl.Mater.Interfaces 2014,6(20),18172-18179]. In addition, the surface of metal oxide nanoparticles prepared by solution method is easy to adsorb water and oxygen in the air, which will cause the "S" shape of the illumination IV curve of the prepared organic solar cell device, which requires long-term illumination or ultraviolet treatment for a certain period of time to eliminate. This "light bath" phenomenon is generally believed to be caused by the interface between the oxide material and the ITO electrode [Nat.Photonics2012,6(2),115-120].

[0004] Silane coupling agent is used to modify the surface of ZnO nanoparticles. In previous reports, it is mostly used in biological applications. After such coating treatment, ZnO nanoparticles can not only be dispersed in green solvents such as water and alcohol, but also greatly improve the fluorescence properties [Sci Rep. 2015, 5, 8475], which is widely used in biological imaging. In addition, after coating with a coupling agent with a specific functional group, it can be further connected with other organic substances [Bull. Mater. Sci. 2012, 1-7]. Similarly, in the field of photovoltaics, researchers also use this type of coupling agent material, generally as a single molecule interface modification layer, to improve the contact between inorganic materials and organic active layers or perovskite layers, to improve device performance [Adv. Funct. Mater. 2010, 20 (24), 4381-4387] [J. Mater. Chem. A 2017, 5 (4), 1658-1666]. However, in the actual preparation process, most of these single-molecule interface modification layers are prepared by spin coating or immersion followed by cleaning. Moreover, as a single-molecule layer, the thickness requirement is more stringent. This not only brings great difficulty to the device preparation process, but also limits the further promotion of its applicability. Summary of the invention

[0005] The main purpose of the present invention is to provide a silane coupling agent modified metal oxide ink and a preparation method thereof, so as to overcome the deficiencies of the prior art.

[0006] Another object of the present invention is to provide a composite material based on metal oxides and fullerene derivatives.

[0007] Another object of the present invention is to provide the use of the metal oxide ink modified by the silane coupling agent, especially in the preparation of optoelectronic devices.

[0008] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0009] The embodiment of the present invention provides a method for preparing a metal oxide ink modified by a silane coupling agent, which comprises:

[0010] First, metal oxide nanoparticles are combined with long alkyl chain organic ligands, and then surface modified with a silane coupling agent having a hydrophilic functional group to form metal oxide nanoparticles modified with a silane coupling agent; the general structural formula of the silane coupling agent is (R 1 O) 3 -Si-R 2 -R 3 , where R 1 Including substituted or unsubstituted C 1 ~C 4 The alkyl group, R 2 Including substituted or unsubstituted C 1 ~C 18 A straight chain or branched chain alkyl group, a substituted or unsubstituted C 2 -C 18 A straight chain or branched alkenyl group with at least one double bond, a substituted or unsubstituted C 2 -C 18 and at least one triple bond, a straight-chain or branched alkynyl group, a substituted or unsubstituted C 3 -C 18 A saturated or at least partially unsaturated cycloalkyl group or one containing no or at least one -NH-, R 3 Including -OH, -NH 2 , vinyl group, acrylate group, epoxy group, halogen group or alkali metal group;

[0011] The metal oxide nanoparticles modified by the silane coupling agent are uniformly dispersed in a second organic solvent to obtain a metal oxide ink modified by the silane coupling agent.

[0012] An embodiment of the present invention also provides a silane coupling agent-modified metal oxide ink prepared by the aforementioned method, which includes silane coupling agent-modified metal oxide nanoparticles and a solvent. The silane coupling agent-modified metal oxide nanoparticles include metal oxide nanoparticles and silane coupling agent groups modified on the surface of the metal oxide nanoparticles.

[0013] The embodiment of the present invention also provides a metal oxide-fullerene derivative composite material, which includes: metal oxide nanoparticles modified by a silane coupling agent, and a fullerene derivative; the metal oxide nanoparticles modified by a silane coupling agent are obtained by chemically modifying the metal oxide nanoparticles via a silane coupling agent;

[0014] Wherein, the general structural formula of the silane coupling agent is (R 1 O) 3 -Si-R 2 -R 3 , where R 1 Including substituted or unsubstituted C 1 ~C 4 The alkyl group, R 2 Including substituted or unsubstituted C 1 ~C 18 A straight chain or branched chain alkyl group, a substituted or unsubstituted C 2 -C 18 A straight chain or branched alkenyl group with at least one double bond, a substituted or unsubstituted C 2 -C 18 and at least one triple bond, a straight-chain or branched alkynyl group, a substituted or unsubstituted C 3 -C 18 A saturated or at least partially unsaturated cycloalkyl group or one containing no or at least one -NH-, R 3 Including -OH, -NH 2 , vinyl group, acrylate group, epoxy group, halogen group or alkali metal group.

[0015] The embodiment of the present invention further provides a metal oxide composite film, which is mainly formed by the metal oxide ink modified by the above-mentioned silane coupling agent or the metal oxide-fullerene derivative composite material.

[0016] Correspondingly, an embodiment of the present invention further provides a method for preparing the aforementioned metal oxide composite thin film, which comprises: forming the metal oxide composite thin film by at least one of coating and printing.

[0017] The embodiments of the present invention also provide uses of the metal oxide ink modified by the silane coupling agent and the metal oxide-fullerene derivative composite material, especially in the preparation of optoelectronic devices.

[0018] The embodiment of the present invention also provides the use of the above metal oxide composite film in preparing optoelectronic devices.

[0019] Furthermore, the optoelectronic device has electrical-optical and / or optical-electrical conversion characteristics and includes a solar cell device or an electroluminescent diode device, etc.

[0020] For example, an embodiment of the present invention further provides an optoelectronic device, including an electrode modification layer, wherein the electrode modification layer includes the aforementioned metal oxide composite thin film.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1) The nano-metal oxide ink modified by the silane coupling agent provided by the present invention has a wide source of raw materials, a short reaction time, low reaction requirements and low cost;

[0023] 2) The nano-metal oxide ink modified by the silane coupling agent of the present invention has good stability. After being placed in an air environment for 8 months, there is no obvious change in particle size. At the same time, it has strong compatibility with fullerene materials and can form a composite material for use in organic solar cells or perovskite solar cells.

[0024] 3) The nano-metal oxide composite film modified by the silane coupling agent provided by the present invention can be deposited by a variety of common methods such as spin coating, blade coating, inkjet printing, etc., and has the advantages of simple processing technology;

[0025] 4) The metal oxide-fullerene derivative composite material of the present invention has good film-forming properties and electrical conductivity, and is cheaper than pure fullerene derivative materials. Its application in perovskite batteries can improve the performance and stability of the batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 This is a process flow chart of preparing a nano metal oxide ink modified by a silane coupling agent in a typical embodiment of the present invention;

[0028] Figure 2 It is the infrared spectra of ZnO@C3 and ZnO@C8 inks prepared in Example 1 and Example 2 of the present invention;

[0029] Figure 3 It is a statistical diagram of particle size distribution of ZnO@C3 and ZnO@C8 inks prepared in Example 1 and Example 2 of the present invention at different storage times;

[0030] Figure 4is a schematic structural diagram of a solar cell device prepared in Example 3 of the present invention;

[0031] Figure 5 is a comparison diagram of JV curves of organic solar cells using ZnO, ZnO@C3, and ZnO@C8 as cathode modification layers in Example 3 of the present invention;

[0032] Figure 6a and Figure 6b This is an AFM image of the composite film formed by ZnO@C3 and C60 fullerene derivative (PC61BM) in Example 4 of the present invention.

[0033] Figure 7 It is a schematic diagram of the device structure of a perovskite solar cell using ZnO@C3 and PCBM composite materials as an electron transport layer in Examples 4 and 5 of the present invention.

[0034] Figure 8 It is a JV curve diagram of the perovskite solar cell using ZnO@C3 / ZnO@C8 and PCBM composite materials as the electron transport layer in Examples 4 and 5 of the present invention.

[0035] Fig. 9 It is an EQE curve diagram of the perovskite solar cell using ZnO@C3 / ZnO@C8 and PCBM composite materials as the electron transport layer in Examples 4 and 5 of the present invention.

[0036] Figure 10a-Figure 10d It is a schematic diagram of the stability of perovskite solar cells using ZnO@C3 / ZnO@C8 and PCBM composite materials as electron transport layers under continuous illumination conditions in Examples 4 and 5 of the present invention. DETAILED DESCRIPTION

[0037] In view of the shortcomings of the prior art, the inventors of this case have proposed the technical solution of the present invention after long-term research and extensive practice, which mainly provides a metal oxide ink modified by a silane coupling agent and a preparation method thereof. The metal oxide ink modified by a silane coupling agent comprises at least one silane coupling agent having an alkyl functional group, metal oxide nanoparticles and a solvent. Among them, the silane coupling agent is preferably selected from methoxy or ethoxy silane, a silane coupling agent whose functional group includes a certain number of alkyl chains and amino groups, and whose terminal group is an alkyl chain. The present invention also discloses the composite material based on the metal oxide, which comprises at least one metal oxide nanoparticle modified by a silicon coupling agent, and at least one fullerene derivative. With the composite material, a composite film can be made by spin coating, printing, etc., and the composite film can be used as an electrode modification layer in optoelectronic devices such as solar cells and light-emitting diodes to improve the contact performance between the electrode and the organic active layer, thereby improving the performance of the optoelectronic device.

[0038] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] One aspect of an embodiment of the present invention provides a composition of a metal oxide ink modified by a silane coupling agent, comprising:

[0040] a metal oxide nanoparticle;

[0041] At least one silane coupling agent having a hydrophilic functional group (R 1 O) 3 -Si-R 2 -R 3 ; Among them, R 1 C 1 -C 4 Alkyl (preferably methyl, ethyl, isopropyl, butyl), R 2 For C 1 -C 18 A straight chain or branched alkyl group having C 2 -C 18 One or more double-bonded straight-chain or branched alkenyl groups, having C 2 -C 18 One or more triple-bonded straight-chain or branched alkynyl groups, having C 3 -C 18 A saturated, partially or fully unsaturated cycloalkyl group, R 3 -OH, -NH 2 , -vinyl, -acrylate group, -epoxy group, -halogen element, -alkali metal, etc.;

[0042] At least one organic solvent.

[0043] Another aspect of an embodiment of the present invention provides a method for preparing a silane coupling agent-modified metal oxide ink, comprising:

[0044] First, metal oxide nanoparticles are combined with long alkyl chain organic ligands, and then surface modified with a silane coupling agent having a hydrophilic functional group to form metal oxide nanoparticles modified with a silane coupling agent; the general structural formula of the silane coupling agent is (R 1 O) 3 -Si-R 2 -R 3 , where R 1 Including substituted or unsubstituted C 1~C 4 The alkyl group, R 2 Including substituted or unsubstituted C 1 ~C 18 A straight chain or branched chain alkyl group, a substituted or unsubstituted C 2 -C 18 A straight chain or branched alkenyl group with at least one double bond, a substituted or unsubstituted C 2 -C 18 and at least one triple bond, a straight-chain or branched alkynyl group, a substituted or unsubstituted C 3 -C 18 A saturated or at least partially unsaturated cycloalkyl group or one containing no or at least one -NH-, R 3 Including -OH, -NH 2 , vinyl group, acrylate group, epoxy group, halogen group or alkali metal group;

[0045] The metal oxide nanoparticles modified by the silane coupling agent are uniformly dispersed in a second organic solvent to obtain a metal oxide ink modified by the silane coupling agent.

[0046] In some preferred embodiments, the R 1 It may preferably include methyl, ethyl, isopropyl or butyl, etc., but is not limited thereto.

[0047] In some preferred embodiments, R 2 For C 1 -C 18 A straight chain or branched alkyl group having C 2 -C 18 One or more double-bonded straight-chain or branched alkenyl groups, having C 2 -C 18 One or more triple-bonded straight-chain or branched alkynyl groups, having C 3 -C 18 The saturated, partially or fully unsaturated cycloalkyl group may contain no or one or more -NH- groups.

[0048] Furthermore, the R 3 -OH, -NH 2 , -vinyl, -acrylate, -epoxy, -halogen, -alkali metal, etc., preferably -NH 2 .

[0049] In some more specific preferred embodiments, the silane coupling agent is a silane coupling agent having an amino-terminated functional group, for example, it may include any one or a combination of two or more of 3-aminopropyltrimethoxysilane (3-aminopropyltrimethoxysilane, APTMS), N-(2-aminoethyl)aminopropyltrimethoxysilane (N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, APTES), 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane (3-[2-(2-Aminoethylamino)ethylamino]propyl-trimethoxysilane, AETPE), etc., but is not limited thereto.

[0050] Furthermore, the silane coupling agent may be propyltrimethoxysilane (C3), n-octyltrimethoxysilane (C8), etc., but is not limited thereto.

[0051] In some preferred embodiments, the preparation method specifically includes: uniformly mixing metal oxide nanoparticles and long alkyl chain organic ligands, reacting at 60-110°C for 2-30 minutes, and dispersing the reactants in a first organic solvent to form a solution of metal oxide nanoparticles coated with long alkyl chain organic ligands, then adding a silane coupling agent and an organic base, heating to 80-100°C to react for 10-60 minutes, and dispersing the reactants in a second organic solvent to obtain a metal oxide ink modified with a silane coupling agent.

[0052] Furthermore, the preparation method specifically includes: dispersing metal oxide nanoparticles in a first solvent, and uniformly mixing long alkyl chain organic ligands according to 0.5-10% of the volume of the nanoparticle dispersion system (i.e., the combination of metal oxide nanoparticles and the first solvent), that is, the volume ratio of the long alkyl chain organic ligand to the combination of metal oxide nanoparticles and the first solvent is 0.5-10:100.

[0053] In some preferred embodiments, the material of the metal oxide nanoparticles can be selected from any one or a combination of two or more of zinc oxide, tin oxide, titanium oxide, zinc oxide, tin oxide, titanium oxide, etc. containing one or more doping elements, but not limited thereto. These oxides have good electron transport properties and are suitable for cathode interface modification. In addition, some other elements doped zinc oxide, titanium oxide, or tin oxide, such as Al, Cs, Mg doped ZnO, In doped SnO 2 Etc., can also be used to modify the cathode of optoelectronic devices. The doping of these elements can improve the work function, carrier concentration and carrier mobility of metal oxides, thereby effectively modifying the cathode modification effect of the device.

[0054] Furthermore, the material of the metal oxide nanoparticles includes any one or a combination of two or more of zinc oxide, tin oxide, titanium oxide, aluminum-doped zinc oxide, cesium-doped zinc oxide, magnesium-doped zinc oxide, indium-doped zinc oxide, indium-doped tin oxide, etc., but is not limited thereto.

[0055] Furthermore, in order to ensure good dispersibility of the metal oxide nanoparticles in the organic solvent, the particle size of the metal oxide nanoparticles is generally 3 to 50 nm, preferably 5 to 15 nm.

[0056] In some preferred embodiments, the end-capping group of the long alkyl chain organic ligand is a carboxyl group or an amino group, preferably any one of oleic acid, oleylamine and hexadecylamine, or a combination of two or more thereof, but not limited thereto. The metal oxide nanoparticles are bound with long alkyl chain organic ligands, which can effectively reduce the agglomeration between the metal oxide nanoparticles, and also help the metal oxide nanoparticles to be well dispersed in the organic solvent. The organic solvent is any one of chloroform, toluene, xylene, trimethylbenzene, chlorobenzene, dichlorobenzene, or a combination of two or more thereof.

[0057] In some preferred embodiments, the mass ratio of the metal oxide nanoparticles to the silane coupling agent is 1:0.1 to 1:0.5, preferably 1:0.1 to 1:0.3. Too high a silane coupling agent ratio will greatly reduce the electrical properties of the metal oxide nanoparticles, while too low a silane coupling agent ratio will make it difficult for the metal oxide nanoparticles to generate clear and stable ink, resulting in the inability to form a dense composite film.

[0058] Further, the first organic solvent includes any one or a combination of two or more of chloroform, toluene, xylene, trimethylbenzene, chlorobenzene, dichlorobenzene, etc., but is not limited thereto.

[0059] Furthermore, the second organic solvent includes any one or a combination of two or more of methanol, ethanol, n-propanol, isopropanol, n-butanol, tert-butanol, ethylene glycol, ethylene glycol monomethyl ether, etc., but is not limited thereto.

[0060] Further, the organic base includes tetramethylammonium hydroxide, but is not limited thereto.

[0061] Furthermore, the molar ratio of the organic base to the metal oxide nanoparticles is 0.05:1 to 0.3:1.

[0062] Among them, in some more specific embodiments, the method for preparing the silane coupling agent modified nano metal oxide ink includes: combining metal oxide nanoparticles with long alkyl chain organic ligands, dispersing them in an organic solvent, performing surface modification using a certain amount of silane coupling agent through ligand exchange, and finally dispersing them in an organic alcohol to form the metal oxide ink.

[0063] Among them, in some more specific embodiments, the preparation method of the silane coupling agent modified metal oxide ink may include the following steps:

[0064] (a) uniformly mixing the metal oxide nanoparticles and the long alkyl chain organic ligand, heating and stirring to react, and dissolving them in a first organic solvent after centrifugal washing to form a clear solution (i.e., a solution of metal oxide nanoparticles coated with the long alkyl chain organic ligand);

[0065] (b) adding a certain amount of silane coupling agent to the clear solution, heating for reaction, centrifugally cleaning, and then ultrasonically dispersing the solution in a second organic solvent to form a composite ink of metal oxide nanoparticles coated with the silane coupling agent.

[0066] Among them, the first organic solvent is any one of chloroform, toluene, xylene, trimethylbenzene, chlorobenzene, dichlorobenzene, etc., or a combination of two or more thereof; the second organic solvent is at least selected from any one of methanol, ethanol, n-propanol, isopropanol, n-butanol, tert-butanol, ethylene glycol, ethylene glycol monomethyl ether, etc., or a combination of two or more thereof.

[0067] Another aspect of an embodiment of the present invention also provides a silane coupling agent-modified metal oxide ink prepared by the aforementioned method, which includes silane coupling agent-modified metal oxide nanoparticles and a solvent. The silane coupling agent-modified metal oxide nanoparticles include metal oxide nanoparticles and silane coupling agent groups modified on the surface of the metal oxide nanoparticles.

[0068] In some preferred embodiments, the concentration (weight / volume concentration) of the metal oxide nanoparticles modified by the silane coupling agent in the metal oxide ink modified by the silane coupling agent is 0.5-60 mg / ml. A lower solid content results in insufficient deposition of the composite during the preparation of the film by the composite ink, and a higher solid content concentration easily leads to solid precipitation.

[0069] The nano metal oxide ink modified by the silane coupling agent of the present invention has good stability, and after being placed in an air environment for 8 months, there is no obvious change in particle size.

[0070] The metal oxide nanomaterial modified by a silane coupling agent of the present invention has good ink stability and strong compatibility with fullerene materials, and can form a composite material for use in organic solar cells or perovskite solar cells.

[0071] Another aspect of the embodiments of the present invention further provides a metal oxide film, which is mainly formed by the metal oxide ink modified by the above-mentioned silane coupling agent.

[0072] Furthermore, the thickness of the metal oxide film is 10-100 nm, and the thickness can be adjusted according to the concentration of the ink.

[0073] Another aspect of the embodiments of the present invention further provides a metal oxide-fullerene derivative composite material, which includes metal oxide nanoparticles modified by a silane coupling agent, and a fullerene derivative; the metal oxide nanoparticles modified by a silane coupling agent are obtained by chemically modifying metal oxide nanoparticles via a silane coupling agent;

[0074] Wherein, the general structural formula of the silane coupling agent is (R 1 O) 3 -Si-R 2 -R 3 , where R 1 Including substituted or unsubstituted C 1 ~C 4 The alkyl group, R 2 Including substituted or unsubstituted C 1 ~C 18 A straight chain or branched chain alkyl group, a substituted or unsubstituted C 2 -C 18 A straight chain or branched alkenyl group with at least one double bond, a substituted or unsubstituted C 2 -C 18 and at least one triple bond, a straight-chain or branched alkynyl group, a substituted or unsubstituted C 3 -C 18 A saturated or at least partially unsaturated cycloalkyl group or one containing no or at least one -NH-, R 3 Including -OH, -NH 2 , vinyl group, acrylate group, epoxy group, halogen group or alkali metal group.

[0075] That is, the metal oxide-fullerene derivative composite material of the present invention comprises:

[0076] at least one metal oxide nanoparticle,

[0077] At least one silane coupling agent having a hydrophilic functional group (R 1 O)3 -Si-R 2 -R 3 , where R 1 Including substituted or unsubstituted C 1 ~C 4 The alkyl group, R 2 Including substituted or unsubstituted C 1 ~C 18 A straight chain or branched chain alkyl group, a substituted or unsubstituted C 2 -C 18 A straight chain or branched alkenyl group with at least one double bond, a substituted or unsubstituted C 2 -C 18 and at least one triple bond, a straight-chain or branched alkynyl group, a substituted or unsubstituted C 3 -C 18 A saturated or at least partially unsaturated cycloalkyl group or one containing no or at least one -NH-, R 3 Including -OH, -NH 2 , vinyl group, acrylate group, epoxy group, halogen group or alkali metal group;

[0078] and a fullerene derivative.

[0079] In some preferred embodiments, the material of the metal oxide nanoparticles can be selected from any one or a combination of two or more of zinc oxide, tin oxide, titanium oxide, zinc oxide, tin oxide, titanium oxide, etc. containing one or more doping elements, but not limited thereto. These oxides have good electron transport properties and are suitable for cathode interface modification. In addition, some other elements doped zinc oxide, titanium oxide, or tin oxide, such as Al, Cs, Mg doped ZnO, In doped SnO 2 Etc., can also be used to modify the cathode of optoelectronic devices. The doping of these elements can improve the work function, carrier concentration and carrier mobility of metal oxides, thereby effectively modifying the cathode modification effect of the device.

[0080] Furthermore, the material of the metal oxide nanoparticles includes any one or a combination of two or more of zinc oxide, tin oxide, titanium oxide, aluminum-doped zinc oxide, cesium-doped zinc oxide, magnesium-doped zinc oxide, indium-doped zinc oxide, indium-doped tin oxide, etc., but is not limited thereto.

[0081] Furthermore, in order to ensure good dispersibility of the metal oxide nanoparticles in the organic solvent, the particle size of the metal oxide nanoparticles is generally 3 to 50 nm, preferably 5 to 15 nm.

[0082] In some preferred embodiments, the fullerene derivative includes any one of a C60 derivative, a C70 derivative, etc., or a combination of two thereof, but is not limited thereto.

[0083] In some preferred embodiments, the mass ratio of the metal oxide nanoparticles modified with the silane coupling agent to the fullerene derivative in the composite material is 0.1:1 to 1:1.

[0084] The metal oxide nanomaterial modified by the silane coupling agent in the present invention has good ink stability and strong compatibility with fullerene materials, and can form a composite material for use in organic solar cells or perovskite solar cells.

[0085] The metal oxide-fullerene derivative composite material of the present invention has good film-forming properties and electrical conductivity, and is cheaper than pure fullerene derivative materials. It is applied in perovskite batteries to improve the performance and stability of the batteries.

[0086] Another aspect of the embodiments of the present invention further provides a metal oxide composite film, which is mainly formed by the above-mentioned metal oxide-fullerene derivative composite material.

[0087] Correspondingly, another aspect of an embodiment of the present invention further provides a method for preparing the aforementioned metal oxide film or metal oxide composite film, which comprises: forming the metal oxide film or metal oxide composite film by at least one of coating and printing.

[0088] In some embodiments, the film-forming method used includes coating or printing. The coating method may include but is not limited to at least any one of the methods such as spin coating, blade coating, and slit coating. The printing method may include but is not limited to at least any one of the methods such as inkjet printing, screen printing, gravure printing, flexographic printing, and flexographic transfer.

[0089] The metal oxide film of the present invention can be deposited by a variety of common methods such as spin coating, blade coating, inkjet printing, etc., and has the advantages of simple processing technology.

[0090] Another aspect of an embodiment of the present invention also provides the use of the aforementioned silane coupling agent modified metal oxide ink, metal oxide-fullerene derivative composite material, the aforementioned metal oxide film (a film formed by a silane coupling agent modified metal oxide ink) or a metal oxide composite film (a composite film formed by a metal oxide-fullerene derivative composite material), in particular, for use in the preparation of optoelectronic devices.

[0091] Further, the optoelectronic device has electrical-optical and / or optical-electrical conversion characteristics and includes a solar cell device or an electroluminescent diode device, etc., but is not limited thereto.

[0092] Furthermore, the solar cell device includes an organic solar cell or a perovskite solar cell, etc., but is not limited thereto.

[0093] In the ink of the present invention, the solvent can be selected according to the use requirements of the device. For example, in perovskite solar cells, butanol or isopropanol can be used as solvents for modifying the fullerene layer; in organic solar cells, organic alcohols or chlorobenzene can be used as solvents to prepare thin films when deposited on ITO electrodes. These functional films include light-emitting layers or electron transport layers in organic electroluminescent devices, active layers or electron transport layers in organic solar cells, or perovskite layers or electron transport layers in perovskite solar cells. Depositing the composite film provided by the present invention on the surface of the above-mentioned functional film can prepare traditional upright organic optoelectronic devices, and can also be used to prepare stacked organic optoelectronic devices, such as stacked OLEDs, stacked organic solar cells, etc.

[0094] The composite film of the present invention can effectively adjust the surface work function of the electrode and improve the interface contact performance between the electrode and the photoelectric active layer by being deposited on the electrode layer. Therefore, the composite film of the present invention can be used in electronic devices with photoelectric conversion characteristics. Typical optoelectronic devices refer to those with electro-optical or optical-electric conversion characteristics, such as solar cell devices and electroluminescent diode devices.

[0095] For example, another aspect of an embodiment of the present invention also provides an optoelectronic device, comprising an electrode modification layer, wherein the electrode modification layer comprises the aforementioned metal oxide thin film (a thin film formed by a metal oxide ink modified by a silane coupling agent) or a metal oxide composite thin film (a composite thin film formed by a metal oxide-fullerene derivative composite material).

[0096] Further, the optoelectronic device has electrical-optical and / or optical-electrical conversion characteristics and includes a solar cell device or an electroluminescent diode device, etc., but is not limited thereto.

[0097] Furthermore, the solar cell device includes an organic solar cell or a perovskite solar cell, etc., but is not limited thereto.

[0098] Furthermore, the organic solar cell comprises a bottom electrode (such as an ITO transparent electrode), a metal oxide film as an electrode modification layer, an organic photoactive layer, a hole transport layer (such as MoO 3 hole transport layer) and a metal top electrode.

[0099] Finally, the present invention also provides a perovskite solar cell structure based on a metal oxide-fullerene derivative composite material as an interface layer and a preparation method thereof.

[0100] Furthermore, the perovskite solar cell includes a bottom electrode (such as an ITO transparent electrode), a hole transport layer (such as PEDOT:PSS), a perovskite photoactive layer, a metal oxide-fullerene derivative composite film as an electrode modification layer, and a metal top electrode, which are arranged in sequence along a set direction.

[0101] In summary, the nano-metal oxide composite ink modified by a silane coupling agent provided by the present invention can effectively reduce the water and oxygen adsorbed on the surface compared with the unmodified ink, and the prepared organic solar cell device can avoid the "light bath" effect, while the device prepared using the unmodified oxide ink needs to be irradiated with ultraviolet light for a certain period of time to eliminate it. In addition, the modified nanoparticles have modified materials between the particles, which greatly reduces the probability of direct contact between the particles, thereby greatly reducing the ink turbidity and even precipitation caused by particle agglomeration. Tests show that the modified metal oxide nanoparticle dispersion can maintain its shape for 12 months at room temperature, and the performance of the prepared solar cell device has not been significantly reduced. The unmodified ink shows obvious sedimentation after being placed for about 3 months, and the performance of the prepared solar cell device is also severely attenuated.

[0102] Among them, further see Figure 1 As shown, in a typical embodiment of the present invention, the technical route of the present invention can be summarized as follows:

[0103] 1. Synthesis of metal oxide nanoparticles (taking zinc oxide as an example):

[0104] Take the synthesis of ZnO nanoparticles as an example: zinc salt is used as raw material, dissolved in anhydrous methanol, heated to 60-65°C, stirred, KOH methanol solution is added dropwise, heated and stirred at a constant temperature of 60°C for 2h to obtain ZnO nanoparticles.

[0105] 2. Metal oxide nanoparticle modification:

[0106] The metal oxide nanoparticles obtained by the reaction are subjected to static precipitation, solvent washing, centrifugal separation, and ultrasonic dispersion in ethanol, and then oleic acid 70 μl / 100 mg is added, heated to 60-110°C and stirred for 2-30 minutes, the reaction is stopped, cooled to room temperature, centrifuged and dissolved in toluene to obtain oleic acid-coated ZnO nanoparticles. Thereafter, a silane coupling agent and an organic base are added, heated to 80-100°C and stirred for 10-60 minutes, the reaction is stopped, cooled to room temperature, centrifuged and ultrasonically dispersed in ethanol to obtain a metal oxide ink modified by a silane coupling agent.

[0107] 3. Preparation of nano metal oxide cathode modification layer based on silane coupling agent modification:

[0108] The metal oxide ink modified by the silane coupling agent can be deposited on the surface of the ITO electrode or the organic photoactive layer by spin coating, scraping, etc. to obtain a cathode modification layer. In some examples, a composite cathode modification layer is spin-coated on the cathode surface in an inverted structure organic photoelectric device.

[0109] The nano-metal oxide composite film modified with a silane coupling agent prepared by the process of the present invention is used as a cathode modification layer of an organic photoelectric device. Compared with traditional cathode modification layer materials, it has better film-forming properties and higher stability, is simple to operate, and has good experimental repeatability. In terms of process, it can be better combined with printing to prepare organic photoelectric devices, and can be used in photoelectric devices to achieve improvements in device performance and long-term stability.

[0110] In order to make the purpose, technical solution and advantages of the present invention more clear, the technical solution of the present invention is further described below in conjunction with the accompanying drawings and several preferred embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention, but the experimental conditions and setting parameters therein should not be regarded as limitations on the basic technical solution of the present invention. And the protection scope of the present invention is not limited to the following embodiments. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0111] Comparative Example 1

[0112] 1. Preparation of ZnO nanoparticles: Take 2.950g zinc acetate dihydrate, dissolve it in 125ml anhydrous methanol, heat and stir to 60℃. Take 1.480g potassium hydroxide, dissolve it in 65ml anhydrous methanol, dissolve it by ultrasonic, and quickly add the methanol solution of potassium hydroxide to the zinc acetate solution drop by drop, and stir it magnetically at 600rpm for 2h under heating conditions of 60-65℃. During the reaction, the solution first changes from colorless, then a white precipitate appears, and then the precipitate gradually disappears, and the solution turns light blue. A white precipitate appears after about 2h. Continue heating for 0.5h, stop heating, the reaction is complete, and it is dispersed in ethanol to form ink.

[0113] 2. The ink is used in organic solar cells. The specific process is as follows: Preparation of an inverted solar cell device with ZnO as the cathode modification layer: The structure of the inverted device includes an ITO cathode, ZnO as the cathode modification layer, PTB7-TH: PC 71 BM photoactive layer, MoO 3 Anode modification layer, Al anode. The device structure is ITO / ZnO / PTB7-TH:PC 71 BM / MoO 3 / A1. The ZnO composite cathode modification layer was spin-coated at 2000 rpm for 1 min and annealed at 124°C in air for 10 min to obtain an inverted solar cell device with ZnO as the cathode modification layer. The JV curve of the organic solar cell can be found in Figure 5 , the device performance parameters can be found in Table 1.

[0114] Example 1: Preparation of ZnO@C3 material

[0115] Where C3 is propyltrimethoxysilane

[0116] The specific operation process of this embodiment is as follows:

[0117] 1. Preparation of ZnO nanoparticles: Take 2.950g zinc acetate dihydrate, dissolve it in 125ml anhydrous methanol, heat and stir to 60℃. Take 1.480g potassium hydroxide, dissolve it in 65ml anhydrous methanol, dissolve it by ultrasonic, and quickly add the methanol solution of potassium hydroxide drop by drop into the zinc acetate solution, and stir it magnetically at 600rpm for 2h under heating conditions of 60-65℃. During the reaction, the solution first changes from colorless, then a white precipitate appears, and then the precipitate gradually disappears, and the solution turns light blue. A white precipitate appears after about 2h. Continue heating for 0.5h, stop heating, and the reaction is complete.

[0118] 2. Preparation of ZnO ethanol dispersion: After the preparation of ZnO nanoparticles, the reaction solution was allowed to stand for 3 hours, the supernatant was removed, 50 ml of anhydrous methanol was added, and the mixture was stirred at 600 rpm for 10 minutes and then allowed to stand overnight; after the supernatant and the white precipitate were completely separated, the supernatant was removed, 50 mL of anhydrous methanol was added, and the mixture was stirred at 600 rpm for 10 minutes, and then centrifuged at 4000 rpm for 10 minutes. The precipitate retained was the ZnO nanoparticles. Anhydrous ethanol was added to the white precipitate, and the dispersion of light blue transparent ZnO nanoparticles was obtained by ultrasonic dispersion, and the concentration was 10 mg / ml after dilution.

[0119] 3. Preparation of ZnO@oleic acid composite ink: After obtaining the ZnO ethanol dispersion, oleic acid was added at a ratio of 70 μl / 100 mg based on the mass of ZnO. After ultrasonication for 10 min, the mixture was heated to 70 °C and stirred for 10 min. The reaction was stopped and cooled to room temperature. After centrifugation, the mixture was dissolved in toluene to obtain a concentration of 10 mg / ml to obtain oleic acid-coated ZnO nanoparticles.

[0120] 4. Preparation of ZnO@C3 composite ink: Take 15 ml of ZnO@oleic acid ink with a concentration of 10 mg / ml, add 2 ml of C3 toluene solution with a concentration of 0.1 mol / L, and 2 ml of tetramethylammonium hydroxide (TMAH) ethanol solution with a concentration of 0.1 mol / L, wherein the mass ratio of ZnO nanoparticles to C3 is 1:0.1, and the molar ratio of tetramethylammonium hydroxide to ZnO nanoparticles is 0.05:1, heat to 85°C to produce a large amount of white precipitate, keep stirring for 15 minutes and then stop the reaction, cool to room temperature, wash with toluene solution 2-3 times, remove excess oleic acid, dissolve it in 15 ml of toluene again, and add 2 ml of TMAH ethanol solution with a concentration of 0.1 mol / L, heat to 85°C, keep stirring for 30 minutes and then stop the reaction, cool to room temperature, centrifuge to remove the solvent, add 15 ml of ethanol, and after ultrasonic treatment, obtain a ZnO@C3 nanomaterial composite ink with a concentration of about 10 mg / ml.

[0121] After testing, the infrared spectrum of the ZnO@C3 ink prepared in the embodiment of the present invention can be found in Figure 2 For the particle size distribution statistics of the ZnO@C3 ink at different storage times, please refer to Figure 3 shown.

[0122] Example 2: Preparation of ZnO@C8 material

[0123] Among them, C8 is n-octyltrimethoxysilane

[0124] The specific operation process of this embodiment is as follows:

[0125] 1. Preparation of ZnO nanoparticles: Take 2.950g zinc acetate dihydrate, dissolve it in 125ml anhydrous methanol, heat and stir to 60℃. Take 1.480g potassium hydroxide, dissolve it in 65ml anhydrous methanol, dissolve it by ultrasonic, and quickly add the methanol solution of potassium hydroxide drop by drop into the zinc acetate solution, and stir it magnetically at 600rpm for 2h under heating conditions of 60-65℃. During the reaction, the solution first changes from colorless, then a white precipitate appears, and then the precipitate gradually disappears, and the solution turns light blue. A white precipitate appears after about 2h. Continue heating for 0.5h, stop heating, and the reaction is complete.

[0126] 2. Preparation of ZnO ethanol dispersion: After the preparation of ZnO nanoparticles, the reaction solution was allowed to stand for 3 hours, the supernatant was removed, 50 ml of anhydrous methanol was added, and the mixture was stirred at 600 rpm for 10 minutes and then allowed to stand overnight; after the supernatant and the white precipitate were completely separated, the supernatant was removed, 50 mL of anhydrous methanol was added, and the mixture was stirred at 600 rpm for 10 minutes, and then centrifuged at 4000 rpm for 10 minutes. The precipitate retained was the ZnO nanoparticles. Anhydrous ethanol was added to the white precipitate, and the dispersion of light blue transparent ZnO nanoparticles was obtained by ultrasonic dispersion, and the concentration was 10 mg / ml after dilution.

[0127] 3. Preparation of ZnO@oleic acid composite ink: After obtaining the ZnO ethanol dispersion, oleic acid was added at a ratio of 70 μl / 100 mg based on the mass of ZnO. After ultrasonication for 10 min, the mixture was heated to 80 °C and stirred for 20 min. The reaction was stopped and cooled to room temperature. After centrifugation, the mixture was dissolved in toluene to obtain a concentration of 10 mg / ml to obtain oleic acid-coated ZnO nanoparticles.

[0128] 4. Preparation of ZnO@C8 composite ink: Take 15 ml of ZnO@oleic acid ink with a concentration of 10 mg / ml, add 2 ml of C8 toluene solution with a concentration of 0.1 mol / L, and 2 ml of tetramethylammonium hydroxide (TMAH) ethanol solution with a concentration of 0.1 mol / L, wherein the mass ratio of ZnO nanoparticles to C8 is 1:0.3, and the molar ratio of tetramethylammonium hydroxide to ZnO nanoparticles is 0.08:1, heat to 80°C to produce a large amount of white precipitate, keep stirring for 15 minutes and then stop the reaction, cool to room temperature, wash with toluene solution 2-3 times, remove excess oleic acid, dissolve it in 15 ml of toluene again, and add 2 ml of TMAH ethanol solution with a concentration of 0.1 mol / L, heat to 80°C, keep stirring for 40 minutes and then stop the reaction, cool to room temperature, centrifuge to remove the solvent, add 15 ml of ethanol, and after ultrasonic treatment, obtain a ZnO@C8 nanomaterial composite ink with a concentration of about 10 mg / ml.

[0129] After testing, the infrared spectrum of the ZnO@C8 ink prepared in the embodiment of the present invention can be found in Figure 2 For the particle size distribution statistics of ZnO@C8 ink at different storage times, please refer to Figure 3 shown.

[0130] Example 3: Application of ZnO@C3 and ZnO@C8 in organic solar cells

[0131] Preparation of inverted solar cell devices with ZnO and ZnO@C3 as cathode modification layers: The structure of the inverted device includes an ITO cathode, ZnO or ZnO@C3 as cathode modification layer, PTB7-TH:PC 71BM photoactive layer, MoO 3 Anode modification layer, Al anode. The device structure is ITO / ZnO (ZnO@C3, ZnO@C8) / PDBD-T: ITIC / MoO 3 / Al, structure as Figure 4 As shown. ZnO, ZnO@C3 and ZnO@C8 are used as electron transport layers, all of which are spin-coated at 2000rpm for 1min and annealed at 124℃ in air for 10min. For the JV curve comparison of organic solar cells using ZnO@C3 and ZnO@C8 as cathode modification layers in this embodiment, please refer to Figure 5 As shown, according to Figure 5 From the JV curves, it can be seen that the performance of the device using ZnO@C3 and ZnO@C8 as the electron transport layer is basically equivalent to that of the device using ZnO as the electron transport layer. The device performance parameters of the organic solar cell with ZnO@C3 and ZnO@C8 as the cathode modification layer obtained in this example can be seen in Table 1.

[0132] Example 4: Preparation and photovoltaic application of ZnO@C3:PCBM composite film

[0133] The preparation of ZnO@C3 material is as in Example 1

[0134] ZnO@C3 was dispersed in toluene solvent to form an ink with a weight concentration of 10 mg / mL, and PCBM was dissolved in chlorobenzene to form an ink with a concentration of 20 mg / mL. ZnO@C3 and PCBM inks were taken and mixed with an appropriate amount of ink according to a weight ratio of ZnO@C3 to PCBM of 0.1:1 to form a composite ink material, and stirred for 5 hours.

[0135] The ZnO@C3:PCBM composite material is used as the electron transport layer of the perovskite solar cell: the device structure is ITO / PEDOT:PSS / PVSK / ZnO@C3:PCBM / Al, and the preparation steps are as follows:

[0136] With ITO as the bottom electrode, PEDOT:PSS, PVSK, and ZnO@C3:PCBM layers were deposited in sequence by spin coating, and Al electrodes were prepared by vacuum evaporation. For the preparation of PEDOT:PSS, PEDOT:PSS (4083) was used as ink, and a film with a thickness of about 30nm was prepared by spin coating at 3500rpm. Subsequently, a perovskite precursor ink with a concentration of 1.35mol / L was dropped on the PEDOT:PSS film layer, and a photoactive layer with a thickness of about 300nm was obtained by spin coating at a speed of 5000rpm. Subsequently, ZnO@C3:PCBM composite ink was dropped on the PVSK film, and an electron transport layer with a thickness of about 40nm was obtained by spin coating at a speed of 2000rpm. Finally, a metal Al with a thickness of about 120nm was obtained by evaporation as the top electrode to complete the preparation of the entire device.

[0137] The AFM image of the composite film formed by ZnO@C3 and C60 fullerene derivative (PC61BM) in this example can be found in Figure 6a and Figure 6b The device structure of the perovskite solar cell with the ZnO@C3 and PCBM composite materials as the electron transport layer prepared in this embodiment can be found in Figure 7 As shown, the JV curve can be found in Figure 8 As shown, the EQE curve can be found in Fig. 9 As shown, the stability diagram of the device under continuous light conditions can be found in Figure 10a-Figure 10d The performance parameters of the perovskite solar cell using the ZnO@C3 and PCBM composite materials as the electron transport layer in this embodiment can be seen in Table 2.

[0138] Example 5: Preparation and photovoltaic application of ZnO@C8:PCBM composite film

[0139] ZnO@C8 was dispersed in toluene solvent to form an ink with a weight concentration of 10 mg / mL, and PCBM was dissolved in chlorobenzene to form an ink with a concentration of 20 mg / mL. ZnO@C8 and PCBM ink were mixed in a volume ratio of 1:5 to form a composite ink material, and stirred for 5 hours.

[0140] The ZnO@C8:PCBM composite material is used as the electron transport layer of the perovskite solar cell: the device structure is ITO / PEDOT:PSS / PVSK / ZnO@C8:PCBM / A1, and the preparation steps are as follows:

[0141] With ITO as the bottom electrode, the PEDOT:PSS, PVSK, and ZnO@C8:PCBM layers were deposited in sequence by spin coating, and the Al electrode was prepared by vacuum evaporation. For the preparation of PEDOT:PSS, PEDOT:PSS (4083) was used as ink, and a film with a thickness of about 30nm was prepared by spin coating at 3500rpm. Subsequently, a perovskite precursor ink with a concentration of 1.35mol / L was dropped on the PEDOT:PSS film layer, and a photoactive layer with a thickness of about 300nm was obtained by spin coating at a speed of 5000rpm. Subsequently, the ZnO@C8:PCBM composite ink was dropped on the PVSK film, and an electron transport layer with a thickness of about 40nm was obtained by spin coating at a speed of 2000rpm. Finally, a metal Al with a thickness of about 120nm was obtained by evaporation as the top electrode to complete the preparation of the entire device.

[0142] The device structure of the perovskite solar cell with the ZnO@C8 and PCBM composite materials as the electron transport layer prepared in this embodiment can be found in Figure 7 As shown, the JV curve can be found in Figure 8 As shown, the EQE curve can be found in Fig. 9 As shown, the stability diagram of the device under continuous light conditions can be found in Figure 10a-Figure 10d The performance parameters of the perovskite solar cell using the ZnO@C8 and PCBM composite materials as the electron transport layer in this embodiment can be seen in Table 2.

[0143] from Figure 8 , Fig. 9 As can be seen from Table 1, when ZnO@C3:PCBM and ZnO@C8:PCBM composite materials are used as electron transport layers, the device performance is significantly improved compared to using PCBM alone as the electron transport layer.

[0144] Moreover, from Figure 10, the continuous light stability data of the device can also show that the stability of the device containing ZnO@C8:PCBM and ZnO@C3:PCBM composite materials as the interface layer is also significantly improved.

[0145] It can be seen that the composite materials based on metal oxides and fullerene derivatives are used in perovskite solar cells to replace conventional PCBM interface layer materials, showing advantages in device performance and stability. In addition, since fullerene derivatives are expensive and metal oxides are cheap, the use of composite materials has obvious advantages in material cost.

[0146] Example 6: Application of the ratio adjustment of metal oxide and fullerene derivative in ZnO@C3:PCBM in perovskite solar cells

[0147] The ZnO@C3:PCBM composite film was prepared according to the method of Example 4. By adjusting the ratio of ZnO@C3 to PCBM to 0.1:1, 0.2:1, 0.3:1, 0.5:1 and 1:1, a device with a structure of ITO / PEDOT:PSS / PVSK / ZnO@C3:PCBM / Al was prepared, and the device performance parameters are shown in Table 2. It can be seen that when the ratio between ZnO@C3:PCBM and PCBM is within 20%, the device performance is excellent.

[0148] Table 1 Device performance parameters of organic solar cells using ZnO, ZnO@C3, and ZnO@C8 as cathode modification layers

[0149]

[0150] Table 2 Performance parameters of perovskite solar cells using ZnO@C3 and PCBM composite materials as electron transport layers in Examples 4 and 6 of the present invention

[0151]

[0152] Example 7: Sn0 2 @C3: Preparation and photovoltaic applications of PCBM composite films

[0153] 1.SnO 2 Preparation of nanoparticles: SnO was synthesized by hydrothermal method. 2 Nanoparticles, as follows: 0.35g SnCl 4 ·5H 2 O and 8 mL of tetrahydroxyammonium hydroxide (TMAH) were added to 3 mL of ethanol in sequence, and ultrasonic stirring was continued for 10 minutes to dissolve, and then heated to 100 ° C and maintained for 12 hours to obtain SnO 2 The obtained sol is then transferred to a water-mixed thermal reactor and maintained at 200°C for 12 hours. The obtained product is centrifuged at high speed and washed several times with deionized water to obtain the obtained nanoparticles.

[0154] 2.SnO 2 Preparation of ethanol dispersion: SnO 2 After the nanoparticles were prepared, the reaction solution was allowed to stand for 3 hours, the supernatant was removed, 50 ml of anhydrous methanol was added, and the mixture was stirred at 600 rpm for 10 minutes and then allowed to stand overnight; after the supernatant and the white precipitate were completely separated, the supernatant was removed, 50 mL of anhydrous methanol was added, and the mixture was stirred at 600 rpm for 10 minutes, and then centrifuged at 4000 rpm for 10 minutes. The precipitate retained was the SnO2 nanoparticles. Anhydrous ethanol was added to the white precipitate, and a light blue transparent SnO2 nanoparticle dispersion was obtained by ultrasonic dispersion, which was diluted to obtain a concentration of 10 mg / ml.

[0155] 3.SnO 2 @ Preparation of oleic acid composite ink: SnO 2 After ethanol dispersion, based on SnO 2 The mass of oleic acid was added at a ratio of 70 μl / 100 mg, and after ultrasonication for 10 min, the mixture was heated to 80 °C and stirred for 30 min. The reaction was stopped, cooled to room temperature, centrifuged and dissolved in toluene to obtain a concentration of 10 mg / ml to obtain oleic acid-coated SnO 2 Nanoparticles.

[0156] 4.SnO 2 Preparation of @C3 composite ink: Take SnO with a concentration of 10 mg / ml 2 @15ml of oleic acid ink, add 2ml of 0.1mol / L C3 toluene solution and 2ml of 0.1mol / L tetramethylammonium hydroxide (TMAH) ethanol solution, where SnO 2 The mass ratio of nanoparticles to C3 is 1:0.2, and the mass ratio of tetramethylammonium hydroxide to SnO 2 The molar ratio of the nanoparticles was 0.05:1, and a large amount of white precipitate was generated after heating to 85°C. The reaction was stopped after stirring for 15 minutes, cooled to room temperature, washed with toluene solution 2-3 times, and after removing excess oleic acid, it was dissolved in 15 ml of toluene again, and 2 ml of 0.1 mol / L TMAH ethanol solution was added, heated to 85°C, stirred for 30 minutes, and then cooled to room temperature. After centrifugation to remove the solvent, 15 ml of ethanol was added, and after ultrasonic treatment, a SnO with a concentration of about 10 mg / ml was obtained. 2 @C3 nanomaterial composite ink.

[0157] 5. SnO 2 @C3 was dispersed in toluene solvent to form an ink with a weight concentration of 10 mg / mL, and PCBM was dissolved in chlorobenzene to form an ink with a concentration of 20 mg / mL. 2 @C3 and PCBM ink, with a weight ratio of 0.5:1, form a composite ink material and stir for 5 hours.

[0158] SnO 2 @C3: PCBM composite material is the electron transport layer of perovskite solar cells: the device structure is ITO / PEDOT:PSS / PVSK / SnO2@C3:PCBM / A1, and the preparation steps are as follows:

[0159] Using ITO as the bottom electrode, PEDOT:PSS, PVSK, SnO were deposited in sequence by spin coating. 2@C3: PCBM layer, and Al electrode prepared by vacuum evaporation. PEDOT:PSS was prepared by using PEDOT:PSS (4083) as ink, and a film with a thickness of about 30nm was prepared by spin coating at 3500rpm. Then, a perovskite precursor ink with a concentration of 1.35mol / L was dropped on the PEDOT:PSS film layer, and a photoactive layer with a thickness of about 300nm was obtained by spin coating at a speed of 5000rpm. Then, SnO 2 @C3: PCBM composite ink is dripped onto the PVSK film, and a 40nm thick electron transport layer is obtained by spin coating at a speed of 2000rpm. Finally, a 120nm thick metal Al is obtained by evaporation as the top electrode to complete the preparation of the entire device.

[0160] Example 8: Preparation and photovoltaic application of AZO@C8:PCBM composite film

[0161] 1. Preparation of AZO nanoparticles: 2 g aluminum nitrate (Al(NO 3 ) 3 -9H 2 O, 16 g zinc acetate (ZnOAc2-2H 2 The AZO nanoparticles were obtained by dissolving the AZO nanoparticles in methanol and stirring for 15 minutes, followed by drying and sintering at 400°C for 2 hours.

[0162] 2. Preparation of AZO ethanol dispersion: After the preparation of AZO nanoparticles, the reaction solution was allowed to stand for 3 hours, the supernatant was removed, 50 ml of anhydrous methanol was added, and the mixture was stirred at 600 rpm for 10 minutes and then allowed to stand overnight; after the supernatant and the white precipitate were completely separated, the supernatant was removed, 50 mL of anhydrous methanol was added, and the mixture was stirred at 600 rpm for 10 minutes, and then centrifuged at 4000 rpm for 10 minutes. The precipitate retained was the AZO nanoparticles. Anhydrous ethanol was added to the white precipitate, and ultrasonic dispersion was performed to obtain a light blue transparent AZO nanoparticle dispersion, which was diluted to obtain a concentration of 10 mg / ml.

[0163] 3. Preparation of AZO@oleic acid composite ink: After obtaining the AZO ethanol dispersion, oleic acid was added at a ratio of 70 μl / 100 mg based on the mass of AZO. After ultrasonication for 10 min, the mixture was heated to 80 °C and stirred for 20 min. The reaction was stopped and cooled to room temperature. After centrifugation, the mixture was dissolved in toluene to obtain a concentration of 10 mg / ml to obtain oleic acid-coated AZO nanoparticles.

[0164] 4. Preparation of AZO@C8 composite ink: Take 15 ml of AZO@oleic acid ink with a concentration of 10 mg / ml, add 2 ml of C8 toluene solution with a concentration of 0.1 mol / L, and 2 ml of tetramethylammonium hydroxide (TMAH) ethanol solution with a concentration of 0.1 mol / L, wherein the mass ratio of AZO nanoparticles to C3 is 1:0.1, and the molar ratio of tetramethylammonium hydroxide to AZO nanoparticles is 0.05:1, heat to 85°C to produce a large amount of white precipitate, keep stirring for 15 minutes and then stop the reaction, cool to room temperature, wash with toluene solution 2-3 times, remove excess oleic acid, dissolve it again in 15 ml of toluene, and add 2 ml of TMAH ethanol solution with a concentration of 0.1 mol / L, heat to 85°C, keep stirring for 30 minutes and then stop the reaction, cool to room temperature, centrifuge to remove the solvent, add 15 ml of ethanol, and after ultrasonic treatment, obtain an AZO@C8 nanomaterial composite ink with a concentration of about 10 mg / ml.

[0165] 5. Disperse AZO@C8 in toluene solvent to form an ink with a weight concentration of 10 mg / mL, and dissolve PCBM in chlorobenzene to form an ink with a concentration of 20 mg / mL. Take AZO@C8 and PCBM inks with a weight ratio of 1:1 to form a composite ink material and stir for 5 hours. Use AZO@C8:PCBM composite material as the electron transport layer of perovskite solar cells: the device structure is ITO / PEDOT:PSS / PVSK / AZO@C8:PCBM / Al, and the preparation steps are as follows:

[0166] With ITO as the bottom electrode, the PEDOT:PSS, PVSK, and AZO@C8:PCBM layers were deposited in sequence by spin coating, and the Al electrode was prepared by vacuum evaporation. For the preparation of PEDOT:PSS, PEDOT:PSS (4083) was used as ink, and a film with a thickness of about 30nm was prepared by spin coating at 3500rpm. Subsequently, a perovskite precursor ink with a concentration of 1.35mol / L was dropped on the PEDOT:PSS film layer, and a photoactive layer with a thickness of about 300nm was obtained by spin coating at a speed of 5000rpm. Subsequently, the AZO@C8:PCBM composite ink was dropped on the PVSK film, and an electron transport layer with a thickness of about 40nm was obtained by spin coating at a speed of 2000rpm. Finally, a metal Al with a thickness of about 120nm was obtained by evaporation as the top electrode to complete the preparation of the entire device.

[0167] Example 9: Preparation of ZnO@C8 material (the ratio of C8 to ZnO is 0.5:1)

[0168] Among them, C8 is n-octyltrimethoxysilane

[0169] The specific operation process of this embodiment is as follows:

[0170] 1. Preparation of ZnO nanoparticles: Take 2.950g zinc acetate dihydrate, dissolve it in 125ml anhydrous methanol, heat and stir to 60℃. Take 1.480g potassium hydroxide, dissolve it in 65ml anhydrous methanol, dissolve it by ultrasonic, and quickly add the methanol solution of potassium hydroxide drop by drop into the zinc acetate solution, and stir it magnetically at 600rpm for 2h under heating conditions of 60-65℃. During the reaction, the solution first changes from colorless, then a white precipitate appears, and then the precipitate gradually disappears, and the solution turns light blue. A white precipitate appears after about 2h. Continue heating for 0.5h, stop heating, and the reaction is complete.

[0171] 2. Preparation of ZnO ethanol dispersion: After the preparation of ZnO nanoparticles, the reaction solution was allowed to stand for 3 hours, the supernatant was removed, 50 ml of anhydrous methanol was added, and the mixture was stirred at 600 rpm for 10 minutes and then allowed to stand overnight; after the supernatant and the white precipitate were completely separated, the supernatant was removed, 50 mL of anhydrous methanol was added, and the mixture was stirred at 600 rpm for 10 minutes, and then centrifuged at 4000 rpm for 10 minutes. The precipitate retained was the ZnO nanoparticles. Anhydrous ethanol was added to the white precipitate, and the dispersion of light blue transparent ZnO nanoparticles was obtained by ultrasonic dispersion, and the concentration was 10 mg / ml after dilution.

[0172] 3. Preparation of ZnO@oleic acid composite ink: After obtaining the ZnO ethanol dispersion, oleic acid was added at a ratio of 70 μl / 100 mg based on the mass of ZnO. After ultrasonication for 10 min, the mixture was heated to 90 °C and stirred for 20 min. The reaction was stopped and cooled to room temperature. After centrifugation, the mixture was dissolved in toluene to obtain a concentration of 10 mg / ml to obtain oleic acid-coated ZnO nanoparticles.

[0173] 4. Preparation of ZnO@C8 composite ink: Take 15 ml of ZnO@oleic acid ink with a concentration of 10 mg / ml, add 2 ml of C8 toluene solution with a concentration of 0.1 mol / L, and 2 ml of tetramethylammonium hydroxide (TMAH) ethanol solution with a concentration of 0.1 mol / L, wherein the mass ratio of ZnO nanoparticles to C8 is 1:0.5, and the molar ratio of tetramethylammonium hydroxide to ZnO nanoparticles is 0.08:1, heat to 80°C to produce a large amount of white precipitate, keep stirring for 15 minutes and then stop the reaction, cool to room temperature, wash with toluene solution 2-3 times, remove excess oleic acid, dissolve it in 15 ml of toluene again, and add 2 ml of TMAH ethanol solution with a concentration of 0.1 mol / L, heat to 80°C, keep stirring for 40 minutes and then stop the reaction, cool to room temperature, centrifuge to remove the solvent, add 15 ml of ethanol, and after ultrasonic treatment, obtain a ZnO@C8 nanomaterial composite ink with a concentration of about 10 mg / ml.

[0174] Example 10: Preparation of AZO@C8:PCBM composite film The weight ratio of AZO@C8 to PCBM is 0.5:1

[0175] Among them, C8 is n-octyltrimethoxysilane

[0176] The preparation of AZO@C8 is as in Example 8.

[0177] AZO@C8 was dispersed in toluene solvent to form an ink with a weight concentration of 10 mg / mL, and PCBM was dissolved in chlorobenzene to form an ink with a concentration of 20 mg / mL. Take AZO@C8 and PCBM inks, take an appropriate volume of ink according to the weight ratio of AZO@C8 to PCBM of 0.5:1, and mix them, and stir for 5 hours. AZO@C8:PCBM composite material is the electron transport layer of perovskite solar cells: the device structure is ITO / PEDOT:PSS / PVSK / AZO@C8:PCBM / Al, and the preparation steps are as follows in Example 8.

[0178] Example 11: TiO 2 @C3: Preparation and photovoltaic applications of PCBM composite films

[0179] 1.TiO 2 Preparation of nanoparticles: First, hydrolyze (Ti(OCH(CH 3 ) 2 ) 4 Obtain TiO 2 Sol; then, 0.4mL of 0.2mol / L hydrochloric acid was diluted into 18mL of ethanol; then, TiO 2 Mix with hydrochloric acid solution and stir in an ice bath for 5 hours to obtain transparent TiO 2 The sol was then diluted ten times and treated in an autoclave at 160°C for 16 hours to obtain TiO 2 Nanoparticles.

[0180] 2.TiO 2 Preparation of ethanol dispersion: TiO 2 After the nanoparticles were prepared, the reaction solution was allowed to stand for 3 h, the supernatant was removed, 50 ml of anhydrous methanol was added, and the mixture was stirred at 600 rpm for 10 min and allowed to stand overnight. After the supernatant and the white precipitate were completely separated, the supernatant was removed, 50 ml of anhydrous methanol was added, and the mixture was stirred at 600 rpm for 10 min, and then centrifuged at 4000 rpm for 10 min. The precipitate retained was TiO 2 Nanoparticles. Anhydrous ethanol was added to the white precipitate and ultrasonic dispersion was performed to obtain light blue transparent TiO 2 The dispersion of nanoparticles was diluted to obtain a concentration of 10 mg / ml.

[0181] 3.TiO 2 @ Preparation of oleic acid composite ink: TiO 2 After ethanol dispersion, TiO 2 The mass of oleic acid was added at a ratio of 70 μl / 100 mg, and after ultrasonication for 10 min, the mixture was heated to 100 °C and stirred for 20 min. The reaction was stopped, cooled to room temperature, centrifuged and dissolved in toluene to obtain a concentration of 10 mg / ml to obtain oleic acid-coated TiO 2 Nanoparticles.

[0182] 4.TiO 2 @C3 Preparation of composite ink: Take TiO with a concentration of 10 mg / ml 2 @15ml of oleic acid ink, add 2ml of 0.1mol / L C3 toluene solution and 2ml of 0.1mol / L tetramethylammonium hydroxide (TMAH) ethanol solution, where TiO 2 The mass ratio of nanoparticles to C3 is 1:0.2, and the mass ratio of tetramethylammonium hydroxide to TiO 2 The molar ratio of the nanoparticles was 0.1:1, and a large amount of white precipitate was generated after heating to 85°C. The reaction was stopped after stirring for 15 minutes, cooled to room temperature, washed with toluene solution 2-3 times, and the excess oleic acid was removed. The mixture was dissolved in 15 ml toluene again, and 2 ml of 0.1 mol / L TMAH ethanol solution was added. The mixture was heated to 85°C, stirred for 40 minutes, and stopped after the reaction. The mixture was cooled to room temperature, centrifuged to remove the solvent, and 15 ml of ethanol was added. After ultrasonic treatment, a TiO2 with a concentration of about 10 mg / ml was obtained. 2 @C3 nanomaterial composite ink.

[0183] 5. TiO 2 @C3 was dispersed in toluene solvent to form an ink with a weight concentration of 10 mg / mL, and PCBM was dissolved in chlorobenzene to form an ink with a concentration of 20 mg / mL. 2 @C3 and PCBM ink, with a weight ratio of 0.5:1, form a composite ink material and stir for 5 hours.

[0184] TiO 2 @C3: PCBM composite material is the electron transport layer of perovskite solar cells: the device structure is ITO / PEDOT:PSS / PVSK / TiO 2 @C3: PCBM / Al, preparation steps are as follows:

[0185] Using ITO as the bottom electrode, PEDOT:PSS, PVSK, TiO 2@C3: PCBM layer, and Al electrode was prepared by vacuum evaporation. PEDOT:PSS was prepared by using PEDOT:PSS (4083) as ink and spin coating at 3500rpm to prepare a film with a thickness of about 30nm. Then, a perovskite precursor ink with a concentration of 1.35mol / L was dropped on the PEDOT:PSS film layer, and spin coating was performed at a speed of 5000rpm to obtain a photoactive layer with a thickness of about 300nm. Then, TiO 2 @C3: PCBM composite ink is dripped onto the PVSK film, and a 40nm thick electron transport layer is obtained by spin coating at a speed of 2000rpm. Finally, a 120nm thick metal Al is obtained by evaporation as the top electrode to complete the preparation of the entire device.

[0186] Example 12: Preparation and photovoltaic application of ITO@C8:PCBM composite film

[0187] 1. Preparation of ITO nanoparticles: First, hydrolyze (Ti(OCH(CH 3 ) 2 ) 4 Obtain TiO 2 Sol; then, 0.4mL of 0.2mol / L hydrochloric acid was diluted into 18mL of ethanol; then, TiO 2 Mix with hydrochloric acid solution and stir in an ice bath for 5 hours to obtain transparent TiO 2 The sol was then diluted ten times and treated in an autoclave at 160°C for 16 hours to obtain ITO nanoparticles.

[0188] 2. Preparation of ITO ethanol dispersion: After the preparation of ITO nanoparticles, the reaction solution was allowed to stand for 3 hours, the supernatant was removed, 50 ml of anhydrous methanol was added, and the mixture was stirred at 600 rpm for 10 minutes and then allowed to stand overnight; after the supernatant and the white precipitate were completely separated, the supernatant was removed, 50 mL of anhydrous methanol was added, and the mixture was stirred at 600 rpm for 10 minutes, and then centrifuged at 4000 rpm for 10 minutes. The precipitate retained was the ITO nanoparticles. Anhydrous ethanol was added to the white precipitate, and the dispersion of light blue transparent ITO nanoparticles was obtained by ultrasonic dispersion, which was diluted to obtain a concentration of 10 mg / ml.

[0189] 3. Preparation of ITO@oleic acid composite ink: After obtaining the ITO ethanol dispersion, oleic acid was added at a ratio of 70 μl / 100 mg based on the mass of ITO. After ultrasonication for 10 minutes, the mixture was heated to 100°C and stirred for 20 minutes. The reaction was stopped and cooled to room temperature. After centrifugation, the mixture was dissolved in toluene to obtain a concentration of 10 mg / ml to obtain oleic acid-coated ITO nanoparticles.

[0190] 4. Preparation of ITO@C8 composite ink: Take 15 ml of ITO@oleic acid ink with a concentration of 10 mg / ml, add 2 ml of C8 toluene solution with a concentration of 0.1 mol / L, and 2 ml of tetramethylammonium hydroxide (TMAH) ethanol solution with a concentration of 0.1 mol / L, wherein the mass ratio of ITO nanoparticles to C8 is 1:0.4, and the molar ratio of tetramethylammonium hydroxide to ITO nanoparticles is 0.10:1, heat to 80°C to produce a large amount of white precipitate, keep stirring for 15 minutes and then stop the reaction, cool to room temperature, wash with toluene solution 2-3 times, remove excess oleic acid, dissolve it in 15 ml of toluene again, and add 2 ml of TMAH ethanol solution with a concentration of 0.1 mol / L, heat to 80°C, keep stirring for 40 minutes and then stop the reaction, cool to room temperature, centrifuge to remove the solvent, add 15 ml of ethanol, and after ultrasonic treatment, obtain an ITO@C8 nanomaterial composite ink with a concentration of about 10 mg / ml.

[0191] The ITO@C8:PCBM composite material is used as the electron transport layer of the perovskite solar cell: the device structure is ITO / PEDOT:PSS / PVSK / ITO@C8:PCBM / A1, and the preparation steps are basically the same as those in Example 8.

[0192] Example 13: TiO 2 Preparation of 3-aminopropyltrimethoxysilane (APTMS) composite ink

[0193] 1.TiO 2 The preparation of nanoparticles is as in Example 11.

[0194] 2.TiO 2 Preparation of ethanol dispersion: TiO 2 After the nanoparticles were prepared, the reaction solution was allowed to stand for 3 h, the supernatant was removed, 50 ml of anhydrous methanol was added, and the mixture was stirred at 600 rpm for 10 min and allowed to stand overnight. After the supernatant and the white precipitate were completely separated, the supernatant was removed, 50 ml of anhydrous methanol was added, and the mixture was stirred at 600 rpm for 10 min, and then centrifuged at 4000 rpm for 10 min. The precipitate retained was TiO 2 Nanoparticles. Anhydrous ethanol was added to the white precipitate and ultrasonic dispersion was performed to obtain light blue transparent TiO 2 The dispersion of nanoparticles was diluted to obtain a concentration of 10 mg / ml.

[0195] 3.TiO 2 @ Preparation of oleic acid composite ink: Get TiO 2 After ethanol dispersion, TiO 2The mass of oleic acid was added at a ratio of 70 μl / 100 mg, and after ultrasonication for 10 min, the mixture was heated to 70 °C and stirred for 10 min, then the reaction was stopped, cooled to room temperature, centrifuged and dissolved in toluene to obtain a concentration of 10 mg / ml to obtain oleic acid-coated TiO 2 Nanoparticles.

[0196] 4.TiO 2 Preparation of APTMS composite ink: Take TiO with a concentration of 10 mg / ml 2 @15ml of oleic acid ink, add 2ml of 0.1mol / L APTMS toluene solution and 2ml of 0.1mol / L tetramethylammonium hydroxide (TMAH) ethanol solution, where TiO 2 The mass ratio of nanoparticles to APTMS is 1:0.1, and the mass ratio of tetramethylammonium hydroxide to TiO 2 The molar ratio of the nanoparticles was 0.2:1, and a large amount of white precipitate was generated after heating to 85°C. The reaction was stopped after stirring for 15 minutes, cooled to room temperature, washed with toluene solution 2-3 times, and the excess oleic acid was removed. The mixture was dissolved in 15 ml toluene again, and 2 ml of 0.1 mol / L TMAH ethanol solution was added. The mixture was heated to 85°C, stirred for 30 minutes, and stopped after cooling to room temperature. After centrifugation to remove the solvent, 15 ml of ethanol was added, and the TiO with a concentration of about 10 mg / ml was obtained after ultrasonic treatment. 2 @APTMS composite ink.

[0197] Example 14: Preparation of ZnO@ethynyltrimethoxysilane (VTMS) composite ink

[0198] 1. The preparation of ZnO nanoparticles is as in Example 1.

[0199] 2. Preparation of ZnO ethanol dispersion: After the preparation of ZnO nanoparticles, the reaction solution was allowed to stand for 3 hours, the supernatant was removed, 50 ml of anhydrous methanol was added, and the mixture was stirred at 600 rpm for 10 minutes and then allowed to stand overnight; after the supernatant and the white precipitate were completely separated, the supernatant was removed, 50 mL of anhydrous methanol was added, and the mixture was stirred at 600 rpm for 10 minutes, and then centrifuged at 4000 rpm for 10 minutes. The precipitate retained was the ZnO nanoparticles. Anhydrous ethanol was added to the white precipitate, and the dispersion of light blue transparent ZnO nanoparticles was obtained by ultrasonic dispersion, and the concentration was 10 mg / ml after dilution.

[0200] 3. Preparation of ZnO@oleic acid composite ink: After obtaining the ZnO ethanol dispersion, oleic acid was added at a ratio of 70 μl / 100 mg based on the mass of ZnO. After ultrasonication for 10 min, the mixture was heated to 110 °C and stirred for 2 min. The reaction was stopped and cooled to room temperature. After centrifugation, the mixture was dissolved in toluene to obtain a concentration of 10 mg / ml to obtain oleic acid-coated ZnO nanoparticles.

[0201] 4. Preparation of ZnO@VTMS composite ink: Take 15 ml of ZnO@oleic acid ink with a concentration of 10 mg / ml, add 2 ml of APTMS toluene solution with a concentration of 0.1 mol / L, and 2 ml of tetramethylammonium hydroxide (TMAH) ethanol solution with a concentration of 0.1 mol / L, wherein the mass ratio of ZnO nanoparticles to APTMS is 1:0.3, and the molar ratio of tetramethylammonium hydroxide to ZnO nanoparticles is 0.3:1, heat to 110°C to produce a large amount of white precipitate, keep stirring for 5 minutes and then stop the reaction, cool to room temperature, wash with toluene solution 2-3 times, remove excess oleic acid, dissolve it in 15 ml of toluene again, and add 2 ml of TMAH ethanol solution with a concentration of 0.1 mol / L, heat to 95°C, keep stirring for 30 minutes and then stop the reaction, cool to room temperature, centrifuge to remove the solvent, add 15 ml of ethanol, and after ultrasonic treatment, obtain a ZnO@VTMS composite ink with a concentration of about 10 mg / ml.

[0202] Example 15: SnO 2 @Preparation of epoxy silane coupling agent (ESCA) composite ink

[0203] 1.SnO 2 The preparation of nanoparticles is as in Example 7.

[0204] 2.SnO 2 Preparation of ethanol dispersion: SnO 2 After the nanoparticles were prepared, the reaction solution was allowed to stand for 3 h, the supernatant was removed, 50 ml of anhydrous methanol was added, and the mixture was stirred at 600 rpm for 10 min and allowed to stand overnight. After the supernatant and the white precipitate were completely separated, the supernatant was removed, 50 ml of anhydrous methanol was added, and the mixture was stirred at 600 rpm for 10 min, and then centrifuged at 4000 rpm for 10 min. The precipitate retained was SnO 2 Nanoparticles. Anhydrous ethanol was added to the white precipitate and ultrasonic dispersion was performed to obtain light blue transparent SnO 2 The dispersion of nanoparticles was diluted to obtain a concentration of 10 mg / ml.

[0205] 3.SnO 2 @ Preparation of oleic acid composite ink: SnO 2 After ethanol dispersion, based on SnO 2The mass of oleic acid was added at a ratio of 70 μl / 100 mg, and after ultrasonication for 10 min, the mixture was heated to 60 °C and stirred for 30 min, then the reaction was stopped, cooled to room temperature, centrifuged and dissolved in toluene to obtain a concentration of 10 mg / ml to obtain oleic acid-coated SnO 2 Nanoparticles.

[0206] 4.SnO 2 Preparation of ESCA composite ink: Take SnO with a concentration of 10 mg / ml 2 @15ml of oleic acid ink, add 2ml of 0.1mol / L APTMS toluene solution and 2ml of 0.1mol / L tetramethylammonium hydroxide (TMAH) ethanol solution, heat to 85℃ to produce a large amount of white precipitate, keep stirring for 15min and stop the reaction, cool to room temperature, wash with toluene solution 2-3 times, remove excess oleic acid, dissolve in 15ml toluene again, add 2ml of 0.1mol / L TMAH ethanol solution, heat to 80℃, keep stirring for 60min and stop the reaction, cool to room temperature, centrifuge to remove the solvent, add 15ml ethanol, and after ultrasonic treatment, obtain SnO with a concentration of about 10mg / ml 2 @ESCA composite ink.

[0207] Example 16: Preparation of ZnO@Mercaptopropyltrimethoxysilane coupling agent (MTSE) composite ink

[0208] 1. The preparation of ZnO nanoparticles is as in Example 1.

[0209] 2. Preparation of ZnO ethanol dispersion: as in Example 1.

[0210] 3. Preparation of ZnO@oleic acid composite ink: as in Example 1.

[0211] 4. Preparation of ZnO@MTSE composite ink: Take 15 ml of ZnO@oleic acid ink with a concentration of 10 mg / ml, add 2 ml of APTMS toluene solution with a concentration of 0.1 mol / L, and 2 ml of tetramethylammonium hydroxide (TMAH) ethanol solution with a concentration of 0.1 mol / L, wherein the mass ratio of ZnO nanoparticles to APTMS is 1:0.3, and the molar ratio of tetramethylammonium hydroxide to ZnO nanoparticles is 0.15:1, heat to 110°C to produce a large amount of white precipitate, keep stirring for 2 minutes and then stop the reaction, cool to room temperature, wash with toluene solution 2-3 times, remove excess oleic acid, dissolve it in 15 ml of toluene again, and add 2 ml of TMAH ethanol solution with a concentration of 0.1 mol / L, heat to 100°C, keep stirring for 10 minutes and then stop the reaction, cool to room temperature, centrifuge to remove the solvent, add 15 ml of ethanol, and after ultrasonic treatment, obtain a ZnO@MTSE composite ink with a concentration of about 10 mg / ml.

[0212] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0213] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0214] The use of headings and sections in this disclosure is not meant to limit the disclosure; each section may apply to any aspect, embodiment, or feature of the disclosure.

[0215] Throughout this disclosure, where a composition is described as having, containing, or comprising particular components, or where a process is described as having, containing, or comprising particular process steps, it is contemplated that the compositions taught by the present invention also consist essentially of or consist of the recited components, and that the processes taught by the present invention also consist essentially of or consist of the recited process steps.

[0216] It should be understood that the order of the various steps or the order in which a particular action is performed is not very important, as long as the teachings of the present invention remain operable. In addition, two or more steps or actions may be performed simultaneously.

[0217] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.

Claims

1. An optoelectronic device, which is an organic solar cell, comprising a bottom electrode, a metal oxide composite film as an electrode modification layer, an organic photoactive layer, a hole transport layer and a top electrode arranged in sequence along a set direction, characterized in that: The metal oxide composite film is formed of a metal oxide-fullerene derivative composite material; the thickness of the metal oxide composite film is 10-100 nm; The metal oxide-fullerene derivative composite material comprises metal oxide nanoparticles modified by a silane coupling agent and a fullerene derivative, wherein the fullerene derivative comprises a C60 derivative and / or a C70 derivative, and the mass ratio of the metal oxide nanoparticles modified by a silane coupling agent to the fullerene derivative in the composite material is 0.1:1 to 1:1; The preparation method of the metal oxide nanoparticles modified by the silane coupling agent comprises: First, metal oxide nanoparticles are combined with long alkyl chain organic ligands, and then surface modified with a silane coupling agent having a hydrophilic functional group to form metal oxide nanoparticles modified with a silane coupling agent; the general structural formula of the silane coupling agent is (R 1 O)3─Si─R 2 ─R 3 , where R 1 Including substituted or unsubstituted C1~C4 alkyl, R 2 Including substituted or unsubstituted C1~C 18 A straight chain or branched alkyl group, a substituted or unsubstituted C2-C 18 and at least one double bond, a straight chain or branched alkenyl group, a substituted or unsubstituted C2-C 18 and at least one triple bond, a straight chain or branched alkynyl group, a substituted or unsubstituted C3-C 18 A saturated or at least partially unsaturated cycloalkyl group or one containing no or at least one -NH-, R 3 including -OH, -NH2, vinyl, acrylate, epoxy, halogen or alkali metal groups; The organic photoactive layer is PTB7-TH:PC 71 BM photoactive layer.

2. The optoelectronic device according to claim 1, characterized in that: The R 1 Including methyl, ethyl, isopropyl or butyl; said R 3 Including -NH2.

3. The optoelectronic device according to claim 1, characterized in that: The silane coupling agent includes any one of 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)aminopropyltrimethoxysilane, and 3-[2-(2-aminoethylamino)ethylamino]propyl-trimethoxysilane, or a combination of two or more thereof.

4. The optoelectronic device according to claim 1, characterized in that The preparation method specifically comprises: uniformly mixing metal oxide nanoparticles and long alkyl chain organic ligands, reacting at 60-110° C. for 2-30 minutes, dispersing the reactants in a first organic solvent to form a solution of metal oxide nanoparticles coated with long alkyl chain organic ligands, then adding a silane coupling agent and an organic base, heating to 80-100° C. for reaction for 10-60 minutes, and dispersing the reactants in a second organic solvent to obtain an ink of metal oxide nanoparticles modified with a silane coupling agent.

5. The optoelectronic device according to claim 1 or 4, characterized in that: The material of the metal oxide nanoparticles includes any one or a combination of two or more of zinc oxide, tin oxide, titanium oxide, zinc oxide containing one or more doping elements, tin oxide containing one or more doping elements, and titanium oxide containing one or more doping elements.

6. The optoelectronic device according to claim 5, characterized in that: The material of the metal oxide nanoparticles includes any one or a combination of two or more of zinc oxide, tin oxide, titanium oxide, aluminum-doped zinc oxide, cesium-doped zinc oxide, magnesium-doped zinc oxide, indium-doped zinc oxide, and indium-doped tin oxide; the particle size of the metal oxide nanoparticles is 3-50 nm.

7. The optoelectronic device according to claim 4, characterized in that: The long alkyl chain organic ligand includes any one or a combination of two or more of oleic acid, oleylamine and hexadecylamine; The volume ratio of the long alkyl chain organic ligand to the combination of the metal oxide nanoparticles and the first solvent is 0.5-10:

100.

8. The optoelectronic device according to claim 4, characterized in that: The mass ratio of the metal oxide nanoparticles to the silane coupling agent is 1:0.1-1:0.

5.

9. The optoelectronic device according to claim 4, characterized in that: The first organic solvent includes any one of chloroform, toluene, xylene, trimethylbenzene, chlorobenzene, and dichlorobenzene, or a combination of two or more thereof; the second organic solvent includes any one of methanol, ethanol, n-propanol, isopropanol, n-butanol, tert-butanol, ethylene glycol, and ethylene glycol monomethyl ether, or a combination of two or more thereof.

10. The optoelectronic device according to claim 4, characterized in that: The organic base includes tetramethylammonium hydroxide; the molar ratio of the organic base to the metal oxide nanoparticles is 0.05:1-0.3:

1.

11. The optoelectronic device according to claim 1, characterized in that The preparation method specifically includes: forming the metal oxide composite film by at least one of coating and printing, the coating method includes at least one of spin coating, blade coating, and slit coating, and the printing method includes at least one of inkjet printing, screen printing, gravure printing, and flexographic printing.